«Omsk group» in exile in Manchuria - M. V. Krotova (Омский научный вестник: Серия "Общество. История. Современность")
Based on unpublished sources and emigrant memoirs, the work analyzes the issue of social adaptation to the conditions of emigration in Manchuria by representatives of the «Omsk group», which consisted of former members of the anti-Bolshevik Siberian governments during the Civil War. Based on the theory of social adaptation and the anthropological approach, the article focuses on such aspects of the biography of this category of figures as behavioral strategies, service on the Chinese Eastern Railway, and the choice of citizenship. The study of the destiny of the “Omichi” in Harbin is necessary to present the activities of Russian public and political figures after the Civil War, to understand the problems of emigration in Manchuria and the peculiarities of the existence of the liberal intelligentsia.